2018
DOI: 10.1371/journal.pone.0204521
|View full text |Cite
|
Sign up to set email alerts
|

Allergy-related disorders (ARDs) among Ethiopian primary school-aged children: Prevalence and associated risk factors

Abstract: BackgroundThere has been a noticeable increase in the prevalence of allergy-related disorders (ARDs) in the modern era. Urbanization is believed to be a major environmental risk factor for the onset of ARDs but data from low- to middle-income countries is limited.ObjectiveOur purpose was to assess the prevalence of ARDs and atopy among a population of rural Ethiopian school children and identify environmental and lifestyle factors associated with such disorders.MethodsWe performed a cross-sectional study on 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
3
6
0
Order By: Relevance
“…Our study showed significant male predominance for the development of AR in the examined age group. This finding is similar to other studies [9,10]. Before the onset of puberty, boys outnumber girls in terms of prevalence, but the trend reverses after puberty.…”
Section: Risk Factors For Cumulative Allergic Rhinitissupporting
confidence: 92%
“…Our study showed significant male predominance for the development of AR in the examined age group. This finding is similar to other studies [9,10]. Before the onset of puberty, boys outnumber girls in terms of prevalence, but the trend reverses after puberty.…”
Section: Risk Factors For Cumulative Allergic Rhinitissupporting
confidence: 92%
“…Similarly, Mehanna et al combined paternal and maternal allergy history into 1 parental category and found that family history of allergies increased the risk of all allergic diseases which made the risk of AR in children with family history 2.8 times higher than that without family history. 22 Environment influence is important to the occurrence of AR. In our study, living in towns or metropolis before 2 years old increased the risk of AR compared with living in rural areas, which could be attributed to vehicle exhaust in urban areas and different lifestyle in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Finding the reasons of different prevalence in different regions of Isfahan needs more epidemiologic studies according to risk factors of AR such as environmental factors (climatic and air quality), types of allergen exposure, and lifestyles (dwellings, exotic foods, pets, and furnishings). [2223]…”
Section: Discussionmentioning
confidence: 99%